Loss of employment, lockdown measures and government responses in malaysia during the Covid-19 pandemic: a note - Habibullah, Muzafar Shah; Saari, Mohd Yusof; Safuan, Sugiharso; Haji Din, Badariah; Bali Mahomed, Anuar Shah (Faculty of Economics and Business, Universiti Malaysia Sarawak, 2021)
In this paper, we use daily administrative data from January 25, 2020 to December 31, 2020 to examine the relationship between job losses and the Malaysian lockdown measures. The Auto Regressive Distributed Lag (ARDL) approach is used to estimate both the long-run and short-run models. The results of the Bounds F-test for cointegration reveal that there is a long-run link between job losses and the Malaysian government lockdown measures (both linear and non-linear). The positive association between job loss and lockdown measures shows that as the lockdown gets tighter, more people will lose their jobs. However, as time passes, especially in conjunction with the government stimulus package programmes, job losses decrease.